Raising awareness of research in palliative care – the roadshow!. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Woodward, Amanda; Nelson, Annmarie; Byrne, Anthony; Moore, Barbara; Evans, Mim; Shankland, Sara
Abstract : Aim: To ensure all specialist palliative care teams are aware of research development and research recruitment opportunities and thus maximise access to palliative care research for all patients in Wales. Method: The Marie Curie Palliative Care Research Centre, Cardiff, collaborated with the Wales Cancer Research Network and NISCHR Cancer Research Group to plan a series of roadshows with palliative care teams across Wales. Initially, a Pilot roadshow was launched at the All Wales Palliative Care Conference, Gregynog in October 2010. This tested, by peer review, the format and content of the series of roadshows planned for 2011. The pilot received constructive feedback and changes were made to ensure the roadshow content was clear and relevant to its intended audience. The roadshows took place at locations selected by the local clinical lead, at lunchtimes, and lasted 1–2 h. The panel of speakers took the audience through a research project from idea to completion, using a real life example. The audience completed feedback forms. Outcome: Feedback was overwhelmingly positive. Several clinicians have contacted the group with their research ideas. Staff have been introduced to their NISCHR Regional Research Nurse Manager. Contact details have been collected and a palliative care database established.